Listening with empathy, caring with dedication: Promoting humanized communication in the context of health - Rozeira, Carlos Henrique Barbosa; Silva, Marcos Fernandes da; Neves, Damiana Pereira da Silva; Possi, Bríscia Rosa Cacemiro; Júnior, Jeová Xavier Rodrigues Palheta; Pastor, Brunélia Rosa Cacemiro; Gava, Sandro; Junior, Evandro Lopes dos Santos; Triaca, Rafael; Figueiredo, Dominik Alves Pries; Domingues, Wimerson Harry Siqueira; Neto, Francisco dos Santos Pimenta (Seven Editora, 2024)
In the health sphere, communication assumes a vital importance, permeating not only the relationship between doctors and patients, but all interactions between health professionals and those they serve. The quality of this communication shapes the understanding of diagnoses, therapeutic decisions, and necessary care. This text delves into the complexity and scope of challenging messages, underlining the imperative of active listening; the training of the entire health team in the art of empathy and in building bonds with their patients; and the effects of communication on physical and mental health, highlighting the urgency of strategies to raise the communicative skills of all involved. The methodology used in this research was epistemological, interdisciplinary, and qualitative, based on the bibliographic search in scientific sources available on digital platforms. The proposed theme aims to promote a more compassionate and patient-centered practice, highlighting the importance of clear, ethical, sensitive, and effective communication in all aspects of health care. DOI:https://doi.org/10.56238/sevened2024.010-012